2018
DOI: 10.1159/000495414
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Corpus Callosotomy Using Laser Interstitial Thermal Therapy for Refractory Epilepsy

Abstract: Corpus callosotomy is a viable treatment for patients with refractory generalized or multifocal epilepsy, particularly those who have drop attacks. Laser interstitial thermal therapy (LITT) is a minimally invasive surgical option for various intracranial lesions. In this report, we present a 2-trajectory thermal ablation using the NeuroBlate® system (Monteris Medical, MN, USA) for an anterior two-thirds callosotomy in a patient with refractory epilepsy and frequent drop attacks. Adequate ablation of the corpus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 20 publications
(25 reference statements)
0
19
0
Order By: Relevance
“…Ball et al reported using LITT for anterior corpus callosotomy in a 21-year-old male. 3 They also used a 2-laser fiber configuration with a posterior approach to the body of the CC. We found an anterior approach to the CC body to be more favorable than a posterior approach as described in the literature to date.…”
Section: Review Of the Literature To Datementioning
confidence: 99%
“…Ball et al reported using LITT for anterior corpus callosotomy in a 21-year-old male. 3 They also used a 2-laser fiber configuration with a posterior approach to the body of the CC. We found an anterior approach to the CC body to be more favorable than a posterior approach as described in the literature to date.…”
Section: Review Of the Literature To Datementioning
confidence: 99%
“…17 Laser interstitial thermal therapy (LITT) is a minimally invasive surgical technique that has shown favorable outcomes in patients with a variety of brain lesions 16,18,26,27,[32][33][34] and has shown favorable outcomes in patients with epilepsy. 1,19,20,35,37,40 Following FDA clearance of two major LITT systems in 2007 (Visualase System, Medtronic Inc.) and 2009 (NeuroBlate System, Monteris Medical Corp.), this technology was first used to treat mesial TLE (mTLE) in 2010 and has been rapidly adapted as one of the neurosurgical tools to manage patients with RE. 4,5,19,22,31,36,40 A recent multicenter study of 234 patients who underwent LITT for mTLE showed that 58% of patients achieved an Engel class I outcome at both 1 and 2 years following LITT.…”
mentioning
confidence: 99%
“…described the use of LITT for corpus callosotomy. 14,15,[19][20][21][22][23][24] The present study constitutes the largest case series of SLACC, with seizure outcomes similar to open callosotomy in 10 patients with LGS.…”
Section: Discussionmentioning
confidence: 71%
“…24 Ball et al and Karsy et al presented case reports of SLACC with favorable outcomes. 19,22 Postoperative discomfort after SLACC was minimal. Postoperative length of hospital stay was <24 hours in eight (80%) of 10 patients.…”
Section: Slacc Versus Open Callosotomymentioning
confidence: 96%